2009
DOI: 10.1016/j.molimm.2009.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The roles of eotaxin and the STAT6 signalling pathway in eosinophil recruitment and host resistance to the nematodes Nippostrongylus brasiliensis and Heligmosomoides bakeri

Abstract: Expulsion of adult Nippostrongylus brasiliensis worms from the small intestine is profoundly impaired in signal transducer and activator of transcription (STAT)6-deficient mice. IL-5 transgenic (Tg) mice with constitutive eosinophilia show profound early resistance in the skin and/or later pre-lung phase of primary infections with N. brasiliensis. This study was designed to assess the importance of the eosinophil chemokine eotaxin and the STAT6/interleukin (IL)-4/IL-13 signalling pathway in early resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…Additionally, our previous studies demonstrated that bone marrow-derived cells expressing STAT6 are required for eosinophil accumulation after a single Alternaria challenge (7). Our current studies show that STAT6 is not required for NHC IL-5 production and suggest that other cell types may produce eosinophil chemoattractants, such as eotaxins, in a STAT6-dependent manner, which may be responsible for the reduction of eosinophils in STAT6 Ϫ/Ϫ mice (18,43,46). Thus NHCs are likely an important source of IL-13 that may subsequently induce STAT6-dependent eotaxin-1 and eotaxin-2 production in other cell types, such as dendritic cells and macrophages, that promote eosinophilia.…”
Section: Discussionmentioning
confidence: 48%
“…Additionally, our previous studies demonstrated that bone marrow-derived cells expressing STAT6 are required for eosinophil accumulation after a single Alternaria challenge (7). Our current studies show that STAT6 is not required for NHC IL-5 production and suggest that other cell types may produce eosinophil chemoattractants, such as eotaxins, in a STAT6-dependent manner, which may be responsible for the reduction of eosinophils in STAT6 Ϫ/Ϫ mice (18,43,46). Thus NHCs are likely an important source of IL-13 that may subsequently induce STAT6-dependent eotaxin-1 and eotaxin-2 production in other cell types, such as dendritic cells and macrophages, that promote eosinophilia.…”
Section: Discussionmentioning
confidence: 48%
“…Immunity against N. brasiliensis rechallenge was impaired in mice made eosinophil deficient by targeted deletion of the erythroid transcription factor (GATA-1) or IL-5 (27,28,43). Mechanistically, IL-33 could promote eosinophilic lung inflammation through inducing IL-5 and IL-13 production from CD4 + T cells and ILC2s (19), or by directly activating eosinophils through TI/ST2.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils are upregulated during Th2 responses, act as a white blood cell defence against helminth infections, and contribute to host resistance to N. brasiliensis and H. p. bakeri during primary and subsequent infections (Janeway, 2008;Knott et al, 2009). We quantified eosinophils by flow cytometry, which provides a quantitative estimate of the proportion of cells in the tissue that are eosinophils.…”
Section: Parasite Infection and Immune Assaysmentioning
confidence: 99%